Recent Advances in the Role of Nuclear Factor Erythroid-2-Related Factor 2 in Spinal Cord Injury: Regulatory Mechanisms and Therapeutic Options - Jiang, Tianqi; He, Yongxiong (Frontiers in Aging Neuroscience, 2022)
Nuclear factor erythroid-2-related factor 2 (Nrf2) is a pleiotropic transcription factor, and it has been documented that it can induce defense mechanisms both oxidative stress and inflammatory injury. At present, more and more evidences show that the Nrf2 signaling pathway is a key pharmacological target for the treatment of spinal cord injury (SCI), and activating the Nrf2 signaling pathway can effectively treat the inflammatory injury and oxidative stress after SCI. This article firstly introduces the biological studies of the Nrf2 pathway. Meanwhile, it is more powerful to explain that activating the Nrf2 signaling pathway can effectively treat SCI by deeply exploring the relationship between Nrf2 and oxidative stress, inflammatory injury, and SCI. In addition, several potential drugs for the treatment of SCI by promoting Nrf2 activation and Nrf2-dependent gene expression are reviewed. And some other treatment strategies of SCI by modulating the Nrf2 pathway are also summarized. It will provide new ideas and directions for the treatment of SCI.